The synergistic effects of recycled polyethylene terephthalate fiber and fly ash on the ductility of one-part geopolymer stabilized soft soil - Zihan Zhou; Guo Hu; Qiang Zhu; Chuanqin Yao; Jun Wu (Case Studies in Construction Materials)
Geopolymer is increasingly recognized as a superior sustainable binder for soft soil stabilization, primarily due to its remarkable strength and reduced environmental footprint. However, soft soil stabilized with geopolymer often exhibits brittle failure under a specific stress state. To enhance ductility, recycled polyethylene terephthalate (PET) fiber, originating from waste plastic, were introduced into one-part geopolymer (OPG)-stabilized soft soil. The effects of PET fiber contents, fiber lengths, and the contents of fly ash (FA) in the OPG binder on the unconfined compressive strength (UCS), compressive stress-strain behavior, compressive strain energy, and failure mode of OPG-stabilized soft soil were comprehensively investigated. The optimum PET fiber content and length, as well as the FA content in the OPG binder, were obtained. Scanning electron microscopy with energy dispersive X-ray spectrometry (SEM-EDS) tests were then employed to study microstructural evolution laws in OPG-stabilized soft soil, providing insights into the synergistic behavior of PET fiber and FA. The experimental results demonstrated that adding FA decreased the UCS and initial stiffness of the sample while incorporating PET fiber further reduced initial stiffness. Nonetheless, the combination of PET fiber and FA significantly improved the ductility behavior of OPG-stabilized soft soil. The optimal FA content was 10 %, with the ideal PET fiber length and content being 9 mm and 1.5 %, respectively. Microstructural analysis revealed that PET fiber can form strong interfacial bonding with geopolymer-soil matrix, generating considerable cohesive and frictional forces. Additionally, FA in the OPG binder not only acted as a dispersant but also altered the orientation of PET fiber relative to the crack front. This synergy allowed PET fiber to fully express their properties, thereby enhancing the ductility of OPG-stabilized soft soil. This study offers theoretical and experimental insight into the application of PET fiber in OPG-stabilized soft soil, contributing to more sustainable and environmentally friendly construction production.